(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Innovation is a driving force behind economic growth, competitiveness, and sustainable development in countries around the world. By fostering a culture of innovation, investing in research and development, and supporting entrepreneurship and small business growth, countries can unlock their potential for innovation-led economic prosperity and improve the lives of their citizens. The paper examines the essence of the concept of innovation infrastructure, its elements, and the importance of innovation for the economic growth of the country.